KECEMASAN SOSIAL PADA MAHASISWA UNIVERSITAS INDONESIA DAN KOREA SELATAN - Chintyasari, Reysya; Shin, Jae-hoon; Wangid, Muhammad Nur; Ekosusilo, Madyo (Jurnal Dikdas Bantara, 2026)
Social anxiety represents a significant mental health concern affecting university students' academic performance and social adjustment globally. This comparative study examines differences in social anxiety prevalence, severity, and contributing factors between Indonesian and South Korean university students. Using a quantitative comparative approach, data were collected from 400 undergraduate students (200 from each country) through the Social Interaction Anxiety Scale (SIAS). Results revealed that South Korean students exhibited significantly higher social anxiety levels (M=42.3, SD=10.2) compared to Indonesian students (M=34.7, SD=11.8; t=7.12, p<.001, d=0.71). Gender differences were more pronounced in South Korea, where female students reported significantly higher anxiety than males (p=.03), while Indonesian students showed no significant gender differences (p=.08). Academic pressure demonstrated stronger correlation with social anxiety in South Korea (r=.49, p<.001) than Indonesia (r=.32, p=.01). These findings underscore the urgent need for targeted mental health interventions and education policy reforms, including culturally-sensitive counseling services, stress management programs, and supportive academic environments in both countries.